Efficacy and safety of lipoprotein apheresis in children with homozygous familial hypercholesterolemia: A systematic review - Luirink, Ilse K.; Schmitt, Claus P. (Journal of clinical lipidology, 2019)
Background - Homozygous familial hypercholesterolemia (HoFH) is a rare genetic disorder that may cause life-threatening cardiovascular disease (CVD) at childhood. Marginal effectiveness of statins in reducing low-density lipoprotein cholesterol (LDL-C) is the reason why extracorporeal removal of LDL-C by lipoprotein apheresis (LA) is recommended at the earliest possible age. - Objective - It is, however, unknown to what extent LA effectively reduces the burden of CVD in children with HoFH. We therefore systemically reviewed the literature on the efficacy and safety of LA in children with HoFH. - Methods - We conducted a systematic literature search using Embase Classic and Embase on studies that evaluated LA in patients with HoFH aged <19 years and reported on at least one of the following outcome measures: cholesterol levels, xanthoma, CVD, or surrogate outcome markers for CVD. Adverse events were also reported on. - Results - We selected 76 studies on 209 patients, 45 of these were case series and 31 were case reports. Mean LDL-C reduction per session was 63% and 71% for nonselective and selective modes of LA, respectively. HDL-C levels were best preserved with selective LA. Xanthomata regressed or disappeared in 83% of patients during LA treatment, surrogate parameters of CVD remained stable in most patients. Of 123 patients, 24 experienced a CVD event of whom 10 had experienced a CVD before LA onset. Six patients died at follow-up. Reported side effects were overall minor. - Conclusion - LA seems to be a safe therapy and substantially reduces LDL-C and xanthomata in children with HoFH. The efficacy with respect to CVD protection as compared with only pharmacologic and dietary treatment remains unclear.
Available online 3 November 2018
Gesehen am 21.05.2019